The cicadas of Argentina with new records, a new genus and fifteen new species (Hemiptera: Cicadoidea: Cicadidae) - Sanborn, Allen F.; Heath, Maxine S. (Zootaxa, 2014)
The Argentine cicada fauna is determined. A total of 108 species belonging to 37 genera, eight tribes, and three subfamilies of cicadas are represented in the Argentine cicada fauna. One genus and 15 species are described as new to science: Torresia Sanborn & Heath gen. n., Fidicinoides ferruginosa Sanborn & Heath sp. n., Proarna alalonga Sanborn & Heath sp. n., Proarna parva Sanborn & Heath sp. n., Prasinosoma medialinea Sanborn & Heath sp. n., Dorisiana noriegai Sanborn & Heath sp. n., Guyalna platyrhina Sanborn & Heath sp. n., Herrera humilastrata Sanborn & Heath sp. n., Herrera umbraphila Sanborn & Heath sp. n., Parnisa lineaviridia Sanborn & Heath sp. n., Parnisa viridis Sanborn & Heath sp. n., Alarcta micromacula Sanborn & Heath sp. n., Torresia lariojaensis Sanborn & Heath sp. n., Torresia sanjuanensis Sanborn & Heath sp. n., Chonosia longiopercula Sanborn & Heath sp. n., and Chonosia septentrionala Sanborn & Heath sp. n. Adusella signata Haupt, 1918 rev. stat. is determined to be a valid species, removed as a junior synonym of Tettigades lebruni Distant, 1906 and reassigned to the genus Odopoea Distant to become Odopoea signata comb. n. Fidicina vinula Stål, 1854 rev. stat. is determined to be a valid species, removed as a junior synonym of Fidicinoides pronoe (Walker, 1850) and assigned to the genus Fidicinoides Boulard & Martinelli to become Fidicinoides vinula comb. n. Proarna capistrata Distant, 1885 rev. stat. is determined to be a valid species, removed as a junior synonym of Proarna montividensis Berg, 1882. Chonosia papa (Berg, 1882) rev. stat. is determined to be a valid species and removed as a junior synonym of Chonosia crassipennis (Walker, 1858). Chonosia crassipennis var. metequei nom. nud. Delétang, 1919 syn. n. is considered natural variation in C. crassipennis. Dorisia bonaerensis var. bergi nom. nud. Delétang, 1919 syn. n. and Dorisia bonaerensis var. dominiquei nom. nud. Delétang, 1919 syn. n. are considered to be natural variation within Guyalna bonaerensis (Berg, 1879). Derotettix proseni Torres, 1945 is determined to be a junior synonym of Derotettix wagneri Distant, 1905 syn. n. Dorisiana metcalfi nom. nov. pro Cicada viridis Olivier, 1790 nec Cicada viridis Linnaeus, 1758 is proposed. Tettigades lizeriana Delétang, 1919 is shown to be an invalid name for the purposes of zoological nomenclature. The first records for Argentina of Fidicinoides determinata (Walker, 1858), Fidicinoides vinula (Stål, 1854) comb. n., rev. stat., Prasinosoma fuembuenai Torres, 1963, Ariasa bilaqueata (Uhler, 1903), Ariasa colombiae (Distant, 1892), Carineta boliviana Distant, 1905, Carineta gemella Boulard, 1986, Calyria stigma (Walker, 1850), Selymbria pandora Distant, 1911, Taphura hastifera (Walker, 1858), Taphura misella (Stål, 1854), and Tettigades angularis Torres, 1958 are provided. Ten species are removed from the Argentine cicada fauna. The new records and new species represent a 36% increase in the known cicada fauna. Fifty-eight species (54%) and 10 genera (27%) are currently endemic to Argentina.